Iman Pribadi dan Komunal: Sebuah Tinjauan Teologis atas Teks Lukas 7:1-10 - Taruna, Rizerius Bintang; Dirgaprimawan, Bernadus (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2023)
Luke 7:1–10 is frequently seen as a story of a miraculous cure. Yet, if we examine more closely, it seems that the text tells of a person’s growing faith, which cannot be isolated from his social surroundings. On the one hand, faith is a matter of one’s connection with God, making it a personal affair. On the other hand, faith is communal since it involves interaction with many people as faith grows. In the text, we encounter three main characters who are trying to participate in bringing a servant healed, through their respective expressions of faith. The first one is the Roman centurion, who commands two different groups to converse with Jesus: some Jewish elders (v.3) and his friends (v.6). These Jewish elders are the second character, and they thank the centurion for being their benefactor (v.5). His friends, who make up the third character, convey his personal long message directly to Jesus (vv. 6-8). This article is interested in examining the intersections between the centurion’s personal faith and the communal faith of these two groups. By employing a narrative criticism, that is a characterization, this article explores how Luke portrays the Roman centurion’s development of faith and how that leads to him influencing the communal faith of the Jewish elders and his friends.ABSTRAK Teks Lukas 7:1-10 umumnya dibaca sebagai kisah mukjizat penyembuhan. Jika kita telaah lebih dalam, rupanya teks tersebut menceritakan tentang kualitas keimanan seseorang yang tidak dapat dipisahkan dari konteks sosialnya. Di satu sisi, iman bersifat pribadi karena menyangkut hubungan individu dengan Tuhan. Di lain sisi, iman bersifat komunal karena melibatkan interaksi dengan banyak orang manakala iman itu bertumbuh. Dalam teks tersebut, kita menjumpai tiga tokoh utama yang sedang mengusahakan kesembuhan seorang hamba, melalui ungkapan imannya masing-masing. Yang pertama adalah si perwira Romawi yang menyuruh dua macam kelompok, yakni beberapa orang tua-tua Yahudi (ay.3) dan sahabat-sahabatnya (ay.6) untuk berinteraksi dengan Yesus. Tokoh kedua adalah orang tua-tua Yahudi yang menyanjung si perwira atas kedermawannya bagi mereka (ay.5). Sedangkan, tokoh ketiga adalah sahabat-sahabatnya yang menyampaikan langsung pan panjang kepada Yesus (ay.6-8). Artikel ini tertarik untuk mengulas bagaimana iman pribadi dari si perwira dan iman komunal dari kedua kelompok saling bersinggungan. Melalui pendekatan naratif, yakni analisis penokohan terhadap ketiga figur di atas, artikel ini hendak menelusuri bagaimana cara Lukas menarasikan proses beriman si perwira Romawi yang kemudian mampu menggerakkan iman komunal tua-tua Yahudi dan sahabat-sahabatnya.